EFFECT OF ELLAGIC ACID ON SOME TYPES OF PATHOGENIC BACTERIA - Ghudhaib, Kadhem K; Hanna, Ekbal R; Jawad, Alaa Hussein (Al-Nahrain Journal of Science, 2010)
Biological activity of ellagic acid toward some pathogenic strains bacteria (Staphylococcusepidermatis, Bacillus cereus, Klebsiella pneumonia and Salmonella typhi) was studied. Theinvestigation was conducted using plate-agar method. Gentamycin and streptomycin were used asstandard drugs. The results show that the biological activity of ellagic acid was more effective thangentamycin and streptomycin.Also, the minimum effective dose of ellagic acid was found to be0.15 mg|ml, while the minimum effective doses of gentamycin and streptomycin were 0.3 mg|mland 2 mg|ml, respectively.